2016
DOI: 10.1590/1679-78252420
|View full text |Cite
|
Sign up to set email alerts
|

Elasto-Plastic Stress Analysis in Rotating Disks and Pressure Vessels Made of Functionally Graded Materials

Abstract: A new elastio-plastic stress solution in axisymmetric problems (rotating disk, cylindrical and spherical vessel) is presented. The rotating disk (cylindrical and spherical vessel) was made of a ceramic/metal functionally graded material, i.e. a particlereinforced composite. It was assumed that the material's plastic deformation follows an isotropic strain-hardening rule based on the von-Mises yield criterion. The mechanical properties of the graded material were modeled by the modified rule of mixtures. By ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 18 publications
(21 reference statements)
0
4
0
Order By: Relevance
“…However, it has been shown that changing these parameters (B r ð Þ, n r ð Þ) has little effect on the strain rate in the Norton equation, 32,51 so in the present work these two parameters are considered constant (B = 4:79 3 10 À22 MPa À6 s À1 , n = 6). 51 By substituting equations (19) and (20) into equation (40), _ e r r i ð Þ and _ e u r i ð Þ are as follows:…”
Section: Creep In Thick-walled Fgm Cylindrical Vesselmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it has been shown that changing these parameters (B r ð Þ, n r ð Þ) has little effect on the strain rate in the Norton equation, 32,51 so in the present work these two parameters are considered constant (B = 4:79 3 10 À22 MPa À6 s À1 , n = 6). 51 By substituting equations (19) and (20) into equation (40), _ e r r i ð Þ and _ e u r i ð Þ are as follows:…”
Section: Creep In Thick-walled Fgm Cylindrical Vesselmentioning
confidence: 99%
“…Evaluation of residual stress distributions in autofrettaged-treated homogenous spherical vessels under different p aut , 9 an analytical study of autofrettage-treated spherical vessels, considering the Bauschinger effect, 10,11 the fatigue life of the vessel during loading and unloading high-pressure cycles (in this study, the fatigue design of a thick-walled Autofrettaged-treated vessel for the food industry, operating at p i = 500 MPa is presented), 12 the analysis of autofrettage of cylinders, 13 and the study of residual stresses and allowable pressure of autofrettaged-treated high-pressure vessels (experimental, numerical, and analytical). 1423 In applied research, a compound cylinder was introduced to increase the residual stress.…”
Section: Introductionmentioning
confidence: 99%
“…[9] used Homotopy Analysis Method (HAM), Adomian Decomposition Method (ADM) and Variational Iteration Method (VIM) under different boundary conditions to provide semi-analytical solutions to the elastic analysis of hollow, functionally graded discs with varying thickness from the center to the ends. [10] and [11] presented a finite element method for elastic-plastic stress solution for a functionally graded rotating disk problem and used Runge-Kutta iteration method as a numerical solution for elasto-plastic stress analysis of rotating disks and pressure vessels made of functionally graded materials. [12] evaluated the elastic deformation analysis of a functionally graded rotating disc using the finite difference method.…”
Section: Introductionmentioning
confidence: 99%
“…Loghman and Shayestemoghadam [ 10 ] obtained history of creep stresses and deformations of a nanocomposite rotating cylinder made of polypropylene reinforced by MWCNTs using Burgers viscoelastic creep model under magneto-thermo-mechanical loadings. Kalali et al [ 11 ] provided an analytical solution for predicting stress components of a strain hardening cylinder based on the von-Mises yield criterion under plane–stress conditions by assuming an isotropic material model. Sharma and Yadav [ 12 ] analyzed thermal creep stresses in thick-walled cylinder with radially varying compressibility under the effect of internal and external pressure.…”
Section: Introductionmentioning
confidence: 99%